Suchtprävention in der Sozialen Arbeit: - Stöver, Heino; Hornig, Larissa (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Why prevention? From what, for whom or against whom? What do we know about prevention from research? What role can social work play in prevention? This textbook provides a modern understanding of preventative work for students and social work practitioners by introducing the concepts of behavioural and situational prevention with reference to drug use. The aim of the book is to present evidence-based strategies of behavioural and situational prevention. For this purpose, our knowledge of realistic, sustainable and thus effective and efficient prevention needs to be strengthened, including by means of many practical examples.